The Rule of Law Shoots Dead where Police Do against Criminals - Aulia Rahman Hasibuan (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
Shooting to death on the spot is carried out by the police in enforcement and security efforts to protect the public and the police from the threat of resistance by criminals. However, in carrying out these actions, it is not uncommon to have legal implications for the police, in other words the police in carrying out these actions cannot be separated from criminal elements. Procedural errors and negligence in using firearms in carrying out police duties are often things that must be held criminally accountable. The responsibility of the police in carrying out the act of shooting to death on the spot against the perpetrators of the crime has a procedure in carrying it out. The procedure for the use of firearms and the authority to shoot and die on the spot carried out by the police are described in the Regulation of the National Police Chief Number 8 of 2009 concerning the Implementation of Human Rights Principles and Standards in the Implementation of the Duties of the Indonesian National Police and in Perkap Number 1 of 2009 concerning the Use of Force in Police Actions. The specification of this research is descriptive analytical, which is a research that aims to provide data that is as accurate as possible about humans, certain conditions or symptoms in relation to laws, regulations, and legal theories that are the object of research. This research method uses this research method using normative juridical research methods, namely by researching library materials which are secondary data and also known as library law research